KAITAN KONDISI MAKROEKONOMI DENGAN NON PERFORMING FINANCING BERDASARKAN SEKTOR EKONOMI PADA PERBANKAN SYARIAH DI INDONESIA - Nunung Nuryartono; Imam Teguh Saptono; Guruh Herman (Jurnal Keuangan dan Perbankan, 2016)
AbstractThis study attempts to identify the effect of macroeconomic variables to Non Performing Financing (NPF)based on economic sector of Islamic banking in Indonesia. The macroeconomic variables used in this study areSertifikat Bank Syariah Indonesia (SBIS), Industrial Production Index (IPI), inflation, and exchange rate.Thedata usedin this studyis amonthly time series data and secondaryin the period January 2009 to December 2014. The analytical method used is Vector Error Correction Model (VECM). Based on the result of simulating Variance Decomposition (VD) and Impulse Response Function (IRF), it is found that, exchange rate tends to be theinnovation of the smallest in the short-term and long-term. The conclusion that in the short term or long term, changes in macroeconomic variables affects the NPF of the four sectors with the amount of variability of thirtyto fifty percent, which NPF agriculture, forestry and agricultural inputs, mining, industry, and transport,storage and communication.